PENGARUH BRAND EXPERIENCE, BRAND SATISFACTION DAN BRAND TRUST TERHADAP BRAND LOYALTY PADA PRODUK APPLE - Henry; Widjaja, William (Publika Citra Media, 2025)
Rapid technological developments have changed the landscape of the electronics and information technology industries, creating increasingly fierce competition between manufacturers. Apple as one of the leading technology companies continues to innovate in delivering high-quality products with a unique user experience. This study aims to analyze the influence of brand experience, brand satisfaction, and brand trust on brand loyalty on Apple products in the era of technological development. This study uses a quantitative approach with a survey method, where data is collected through a questionnaire distributed to 142 respondents who use Apple products. Respondents were selected using a purposive sampling technique with the criteria of using Apple products and processed using SmartPLS 4.0 software. The results show that brand experience and brand satisfaction have a significant influence on brand loyalty. But brand trust has a positive and insignificant effect on brand loyalty.